Untenable Cultural Delimitation in Abdulrazak Gurnah’s Paradise - Panta, Shiva Raj (DMC Journal, 2024)
This research article attempts to explore and examine cultures and their inability to contain the interests and preferences of the individuals and groups that follow them. The objective of this article is to examine the scenes of cultural prescriptions in the fictional setting. This examination, in turn, yields the claim that cultures cannot accommodate the adherents’ preferences, wishes, and interests. Wolfgang Welsch’s theoretical concept of untenable cultural delimitation is employed in the exploration and examination. A culture, in the pragmatic field, is considered to have its boundary; nonetheless, it does not have the edge, upon closer examination. Untenable cultural delimitation as a concept, thus, refers to the cultures’ failure in setting their boundaries. The corpus of the study is chosen to be Paradise by Abdulrazak Gurnah which discusses the interaction between and among certain cultural groups. The cross-case and within-case analysis for the development of themes is employed. The analytical framework for the exploration has been twofold: states of undress and the desire for distinctiveness in terms of attires. This framework is representative of the theme of untenable cultural delimitation in that the state of undress is not culturally appropriate and the desire for distinctiveness is a matter of an individual’s aspirations which are not containable in a given culture. Informed by a research question: What happens to the cultures when the adherents’ interests, preferences, wishes, and interests cannot be accommodated? The study, with the theoretical explanations along with the review and analysis of evidence, establishes that Gurnah’s Paradise is a statement of untenable cultural delimitation. The characters go against the cultural prescriptions thereby perpetuating the notion of the evolutionary nature of a culture. This study turns out to be significant as it contributes to the critical debate on the nature of culture.